Adaptive morpho-traits, taxonomy and biogeography of Metania Gray, 1867 (Porifera: Spongillina: Metaniidae) with the description of a new species from Madagascar - Manconi, Renata; Cadeddu, Barbara; Pronzato, Roberto (Zootaxa, 2015)
A comparative analysis of gemmular architecture adaptive morpho-traits at family level is reported for Metaniidae together with the discovery and description of a new species from the River Mangoky (High Plateau), Madagascar. The new Malagasy species, ascribed to Metania for diagnostic traits of the skeleton and the gemmular architecture, differs from all the other known species of the genus in its unique combination of diagnostic traits. Metania madagascariensis sp. nov. is characterised by encrusting growth form, conulose surface, specialized ectosomal skeleton, alveolate-reticulate choanosomal skeleton, two types of megascleres as smooth oxeas (α) and acanthoxeas (β) ornamented with spines and/or tubercles, one type of microsclere as acanthoxeas with dense spines/tubercles bearing rosettes of microspines at tips; gemmules with or without cage of megascleres and frequently surrounded by microscleres; gemmular theca trilayered with pneumatic layer of fibrous spongin, boletiform (trumpet-like) gemmuloscleres with proximal true rotule large, smooth and with irregular blunt margins, and distal knob-like pseudorotule notably smaller, with a few hooks at the margins. M. madagascariensis belongs to the Afrotropical species group of Metania. Identification keys and an annotated checklist at global level are also provided together with a species-level discussion of Metania focusing on morphology, taxonomy, nomenclature and biogeography.